Psychometric properties of 12-item self-administered World Health Organization disability assessment schedule 2.0 (WHODAS 2.0) among general population and people with non-acute physical causes of disability - systematic review - Saltychev Mikhail; Katajapuu Niina; Bärlund Esa; Laimi Katri (Taylor & Francis, 2022)
Objective: WHODAS 2.0 is a unified scale to measuring disability across diseases, countries, and cultures. The objective was to explore the available evidence on the psychometric properties of 12-item self-administered WHODAS 2.0 among a general population and people with non-acute physical causes of disability.
Methods: Five databases Medline, Embase, Web of Science, Scopus, and PsycINFO were searched for papers related to the validity, reliability, responsiveness, minimal clinically important difference or minimal detectable change of 12-item self-administered WHODAS 2.0. In order to avoid missing any potentially relevant studies, the search clauses were left as generic as possible and the refining search was conducted manually. As the review was focusing on chronic physical disorders and general adult population, major psychiatric diagnoses, acute traumas, other acute conditions (e.g., postpartum or pregnancy), hearing loss, progressive neurological disorders, and age <19 years were excluded. The relevancy of the studies was assessed by two independent reviewers.
Results: The 14 out of 191 observational studies were considered relevant. The sample sizes varied from 80 up to 31,251 participants. Great diversity was observed in the participants’ health problems. The Cronbach’s alpha was high – up to 0.96. The correlations between WHODAS 2.0 and other disability scales were high. Substantial floor without ceiling effect was reported by two studies. Exploratory factor analysis resulted in a multidimensional structure – up to five factors. The discriminative ability and test–retest reliability of the scale was good.
Conclusions: It seems, that the 12-item self-administered WHODAS 2.0 is internally consistent and a reliable scale demonstrating overall good correlation with other measures of disability. However, it appears that it is a multidimensional scale and its total score may represent different combinations of several contributing factors. Thus, the 12-item WHODAS 2.0 can be more reliable when creating a person’s functional profile formed by the 12 individual item scores instead of a single total sum.